الزيادة وأثرها في الاسم المختوم بألف ونون لغير إعراب: دراسة تأصيلية صرفية في مدوّنة "الأدب الصغير" لابن المقفع/ Addition and its effects in nouns ending with non-grammatical alif and nūn suffixes: Establishing its morphological basis from the note of Ibn - binti Abdul Aziz Al-Khudhair, Maha (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2020)
مُلخَّص البحث تتناول هذه الدراسة موضوع الزيادة وأثرها في الاسم المختوم بألف ونون لغير إعراب دراسة تأصيلية صرفية في مدوَّنة الأدب الصغير لابن المقفع، معتمدة المنهج الوصفي التحليلي في تتبع مادتها التي قُسِّمت وِفقَاً لنوع الكلمة، يتقدمها التعريف بابن المقفع وإسهاماته العلمية، وخُتمت بخاتمة لخصت نتائجها، وقد تنوعت مواضعها وفقاً لتنوع مدخولها؛ فكان هناك الزيادة في اسم الجنس، ثم الزيادة في الجموع، فالزيادة في المصادر والمشتقات. وكان من نتائج الدراسة: بيان الأثر الكبير لأحرف الزيادة في معاني الألفاظ ومبانيها، وما يترتب عليه من أثر إعرابي وما ينشأ عن الزيادة من ظواهر صرفية كالعدول بين الصيغ والاستثقال والإعلال والإبدال في اللفظة الواحدة، مع مراعاة أمن اللبس، ونبهت إلى أن الاختلاف في الحكم بزيادة الألف والنون أو أصالتها مبني على اختلاف العلماء حول تأصيل بعض هذه الألفاظ، وأبانت عن الدور الوظيفي الذي تؤديه أحرف الزيادة بعد دخولها على الألفاظ. وقد أبرزت الدراسة العلاقة الكبرى بين مستويات اللغة: الصوتي والصرفي والمعجمي، وهي بذلك تقدم خدمة عظمى لمدوني معاجم الألفاظ؛ مما يدفع إلى التوصية بتكثيف الدراسات في الزوائد على مواد المعاجم لرصد التغييرات التي لحقت أبنيتها وأثرها على المعنى. الكلمات المفتاحية: أثر، الزيادة، الاسم المختوم بألف ونون، تأصيل. Abstract This research attempts to discover the fundamentals about the addition of affixes and their effects on the nouns that ended with “alif” and “nūn”, in a note entitled Al-Adab Al-Ṣaghīr written by Ibn Al-Muqaffaʽ. The research follows analytical and descriptive approaches in analyzing the book according to the types of the word. The study is preceded by the life of Ibn al-Muqaffaʽ, his contributions in the field of knowledge, and concluded with the summary of the results of this research. The suffixes places of attachment with the words varied according to their types. There was the addition in the nouns, in the multitudes, in plural and derivatives. Among the conclusion of the research: the addition would have significant effect on the meaning and structure of the words. The grammatical and morphological meanings are also affected resulting in the changes of the word morphological structure to take into consideration the disambiguation of meaning; the difference on the ruling of adding the (alif) and (nūn) is due to the differences of scholars about the origin of some of these expressions; it indicated the functional role that the additional letters play after being added to the words. The research also highlights on the relationship between the different language levels in Arabic: the phonetic, grammar and lexis. As a result, it provides great service to lexicographers. Key words: Affect, addition, nouns ends with alif and nūn. Abstrak Kajian ini berusaha untuk mengenalpasti asas-asas penambahan imbuhan akhir dan kesannya pada kata nama yang diakhiri dengan "alif" dan "nun", dalam catatan berjudul Al-Adab Al-Ṣaghīr yang ditulis oleh Ibn Al-Muqaffaʽ. Kajian ini menggunakan pendekatan analitis dan deskriptif dalam menganalisis nota tersebut mengikut kategori-kategori perkataan. Kajian ini dimulakan dengan kehidupan Ibn al-Muqaffaʽ, sumbangannya dalam bidang pengetahuan, dan diakhiri dengan ringkasan hasil kajian ini. Tempat gabungan imbuhan akhir ini mereka dengan perkataan-perkataan berbeza-beza mengikut jenis akhiran. Bentuk-bentuk penambahan trdapat dalam kata nama, dalam bentuk jamak dan dalam kata terbitan. Di antara kesimpulan kajian ini: penambahan akan memberi kesan yang signifikan terhadap makna dan struktur kata-kata. Makna tatabahasa dan morfologi juga terkesan mengakibatkan perubahan pada struktur morfologi untuk menjelaskan makna; perbezaan pada hukum penambahan (alif) dan (nun) adalah disebabkan oleh perbezaan sarjana bahasa mengenai asal usul beberapa ungkapan ini; ia menunjukkan peranan fungsional yang dimainkan oleh huruf tambahan setelah ditambahkan pada kata-kata. Penyelidikan ini juga menyoroti hubungan antara tahap bahasa yang berbeza dalam bahasa Arab: fonetik, tatabahasa dan leksis. Kesannya, ia turut memberikan manfaat yang besar kepada ahli leksikografi. Kata kunci: Kata nama, penambahan kesan berakhir dengan alif dan nūn.